Validation of Sience, Technology, Engineering, and Matemathic Based Diagnostik Assessment on Natural Resource Material for Phase B Elementary School Students using Rasch Model - Jihan Nadhifa Dewi; Siti Patonah*; Sukamto Sukamto (Universitas Syiah Kuala, 2023)
One of the ways to design learning the implementation of the independent curriculum is assessment diagnostic. This study aims to develop STEM-based questions to measure students' critical thinking skills. The questions are used for the initial assessment of science subject material